Peningkatan SDM Melalui Pelatihan Kepenulisan dan Self-Publishing Bagi Generasi Muda Sengkang Kab. Wajo - Sumangelipu, Andi (ADPERTISI, 2023)
Increasing human resources or HR is achieved by development methods related to knowledge, skills and abilities through education and training, in this case training. Writing and self-publishing training for the young generation aims to improve (1) literacy skills, (2) ability to process information, (3) ability to disseminate and publish information through self-publishing. This activity was carried out on September 10-11, 2023 and was attended by 20 young people from HMI Wajo Maju Branch, Wajo Regency.